Restorative Justice Facilitation: An Appreciative Inquiry Into Effective Practice for Aotearoa/New Zealand Facilitators - Murray, Winifred Mary (Auckland University of Technology, 2012)
“What do restorative justice facilitators in the criminal justice system in Aotearoa/New Zealand consider to be effective practice?” is the question this thesis seeks to answer. The research investigates how facilitators – the lynchpins in a restorative justice process in the criminal justice system – contribute to restoration of just relationships between adult victims, offenders and their communities. It is an evaluation using an appreciative inquiry methodology with a positive, face-to-face, storytelling approach congruent with restorative justice practice, a practitioner/researcher position and Māori and Pacific perspectives. Data was gathered from focus groups and interviews with key informants. The importance of facilitators in the restorative justice process is examined and new links made between recognised practical facilitation skills, group facilitation theory and restorative justice practice. Policies and actions of successive governments of Aotearoa/New Zealand in the field of restorative justice in the criminal justice system, 2000-2011 are also studied. A thematic analysis of the data gathered, along with the theoretical information discussed, demonstrates the complexity of facilitation in restorative justice practice. Five crucial attributes of effective facilitators emerged: personal presence; awareness of their own self and the wider community; a wide range of facilitation skills; knowledge about restorative justice and where it fits in the social and political context; and personal, collegial and organisational support. Research participants suggest a number of policy changes which would improve the effectiveness of facilitators in restorative justice. These include adequate recognition of and funding for professional restorative justice practice; training for effective facilitation appropriate to European, Māori and Pacific perspectives; and an evaluation of the current state of restorative justice, as well as the development of a plan for its systematic growth and promotion in the criminal justice system.
Keywords: Restorative justice; facilitation; appreciative inquiry; Aotearoa/New Zealand